Synthesis and Evaluation of [18F]FEtLos and [18F]AMBF3Los as Novel 18F-Labelled Losartan Derivatives for Molecular Imaging of Angiotensin II Type 1 Receptors - Martha Sahylí Ortega Pijeira; Paulo Sérgio Gonçalves Nunes; Sofia Nascimento dos Santos; Zhengxing Zhang; Arian Pérez Nario; Efrain Araujo Perini; Walter Miguel Turato; Zalua Rodríguez Riera; Roger Chammas; Philip H. Elsinga; Kuo-Shyan Lin; Ivone Carvalho; et al. (Molecules, 2020)
Losartan is widely used in clinics to treat cardiovascular related diseases by selectively blocking the angiotensin II type 1 receptors (AT1Rs), which regulate the renin-angiotensin system (RAS). Therefore, monitoring the physiological and pathological biodistribution of AT1R using positron emission tomography (PET) might be a valuable tool to assess the functionality of RAS. Herein, we describe the synthesis and characterization of two novel losartan derivatives PET tracers, [18F]fluoroethyl-losartan ([18F]FEtLos) and [18F]ammoniomethyltrifluoroborate-losartan ([18F]AMBF3Los). [18F]FEtLos was radiolabeled by 18F-fluoroalkylation of losartan potassium using the prosthetic group 2-[18F]fluoroethyl tosylate; whereas [18F]AMBF3Los was prepared following an one-step 18F-19F isotopic exchange reaction, in an overall yield of 2.7 ± 0.9% and 11 ± 4%, respectively, with high radiochemical purity (>95%). Binding competition assays in AT1R-expressing membranes showed that AMBF3Los presented an almost equivalent binding affinity (Ki 7.9 nM) as the cold reference Losartan (Ki 1.5 nM), unlike FEtLos (Ki 2000 nM). In vitro and in vivo assays showed that [18F]AMBF3Los displayed a good binding affinity for AT1R-overexpressing CHO cells and was able to specifically bind to renal AT1R. Hence, our data demonstrate [18F]AMBF3Los as a new tool for PET imaging of AT1R with possible applications for the diagnosis of cardiovascular, inflammatory and cancer diseases.